Patient Knowledge and Expectations About Return of Genomic Results in a Biomarker-Driven Master Protocol Trial (SWOG S1400GEN). Issue 11 (November 2021) - Roth, Joshua A.; Trivedi, Meghna S.; Gray, Stacy W.; Patrick, Donald L.; Delaney, Debbie M.; Watabayashi, Kate; Litwin, Paul; Shah, Parth; Crew, Katherine D.; Yee, Monica; Redman, Mary W.; Unger, Joseph M.; et al.
Abstract : PURPOSE: Biomarker-driven master protocols represent a new paradigm in oncology clinical trials, but their complex designs and wide-ranging genomic results returned can be difficult to communicate to participants. The objective of this pilot study was to evaluate patient knowledge and expectations related to return of genomic results in the Lung Cancer Master Protocol (Lung-MAP). METHODS: Eligible participants with previously treated advanced non–small-cell lung cancer were recruited from patients enrolled in Lung-MAP. Participants completed a 38-item telephone survey ⩽ 30 days from Lung-MAP consent. The survey assessed understanding about the benefits and risks of Lung-MAP participation and knowledge of the potential uses of somatic testing results returned. Descriptive statistics and odds ratios for associations between demographic factors and correct responses to survey items were assessed. RESULTS: From August 1, 2017, to June 30, 2019, we recruited 207 participants with a median age of 67, 57.3% male, and 94.2% White. Most participants "strongly/somewhat agreed" with statements that they "received enough information to understand" Lung-MAP benefits (82.6%) and risks (69.5%). In items asking about potential uses of Lung-MAP genomic results, 87.0% correctly indicated that the results help to select cancer treatment, but < 20% correctly indicated that the results are not used to confirm cancer diagnosis, would not reveal risk of developing diseases besides cancer, and would not indicate if family members had increased cancer risk. There were no associations between sociodemographic factors and proportions providing correct responses. CONCLUSION: In a large National Clinical Trials Network biomarker-driven master protocol, most participants demonstrated incorrect knowledge and expectations about the uses of genomic results provided in the study despite most indicating that they had enough information to understand benefits and risks.